Verification of H5 and IL-15 gene integrations in recombinant fowlpox viruses - Nor Majid, Nadzreeq; Abdul Razak, Mariatulqabtiah; Roslan, Nurhidayah; Omar, Abdul Rahman (2015)
Introduction of the chicken cytokine gene might trigger a stronger cellular mediated immune response in recombinant fowlpox viruses already carrying the avian influenza H5 gene. In order to ascertain that integrated H5 and IL-15 genes are stable in the previously constructed recombinant fowlpox viruses, PCR analyses were done after a few viral passages. Wild type fowlpox virus, recombinant fowlpox viruses co-expressing avian influenza H5 (rFWPV/H5) and recombinant fowlpox viruses co-expressing avian influenza H5 and chicken IL-15 cytokine (rFWPV/H5) were propagated in CEF cell culture. DNA genomic extractions were done prior to PCR analysis. Primer set targeting H5 and IL-15 confirmed the deduced sizes of both genes. Flanking primers further verified the stable integration of H5 and IL-15 genes in both recombinant viruses. This study confirms that H5 and IL-15 genes were stably present rFWPV/H5 and rFWPV/H5/IL-15. The current results allow future in vitro and in vivo characterisation of the recombinant viruses in triggering humoral and cellular immune responses.